Stratifikasi Sosial pada Tokoh-Tokoh Naskah Drama Nyonya-Nyonya Karya Wisran Hadi - Solahudin, Satiri; Zahrani, Nadilah (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2022)
In every society, it is not strange for us to find the existence of different levels of social class or social position. Starting from the existence of class differences in society, an idea emerged, namely social stratification. Social stratification takes many forms. However, the researcher chose social stratification based on the class level in the society, criteria of honor, economy, and position or status in the society. The researcher proves the forms of social stratification through dialogue contained in the drama script of Nyonya-nyonya. The purpose of this study is to describe the social stratification depicted in Wisran Hadi's drama Nyonya-Nyonya. The research method used in this study is qualitative descriptive method with a notetaking technique. The results of the analysis prove that every character in the drama script of Nyonya-Nyonya contains forms of social stratification which are depicted through dialogue. The data in this study are 11 data, including the form of social stratification for upper class, middle class, upper class with honor criteria, as well as aspects of ascribed status and achieved status.